Pharmacologic therapies of ARDS: From natural herb to nanomedicine - Meng, Linlin; Liao, Ximing; Wang, Yuanyuan; Chen, Liangzhi; Gao, Wei; Wang, Muyun; Dai, Huiling; Yan, Na; Gao, Yixuan; Wu, Xu; Wang, Kun; Liu, Qinghua (Frontiers in Pharmacology, 2022)
Acute respiratory distress syndrome (ARDS) is a common critical illness in respiratory care units with a huge public health burden. Despite tremendous advances in the prevention and treatment of ARDS, it remains the main cause of intensive care unit (ICU) management and the mortality rate of ARDS remains unacceptably high. The poor performance of ARDS is closely related to its heterogeneous clinical syndrome caused by complicated pathophysiology. Based on the different pathophysiology phases, drugs, protective mechanical ventilation, conservative fluid therapy, and other treatment have been developed to serve as the ARDS therapeutic methods. In recent years, there has been a rapid development in nanomedicine, in which nanoparticles as drug delivery vehicles have been extensively studied in the treatment of ARDS. This article provides an overview of pharmacologic therapies for ARDS, including conventional drugs, natural medicine therapy, and nanomedicine. Particularly, we discuss the unique mechanism and strength of nanomedicine which may provide great promises in treating ARDS in the future.